Using a "child's‐eye view" of social success to understand the importance of school readiness at the transition to formal schooling. Issue 1 (28th August 2018) - Fink, Elian; Browne, Wendy V.; Hughes, Claire; Gibson, Jenny
Abstract: Recent research into school readiness has highlighted the importance of not only children's cognitive and socio‐emotional skills, but also the degree to which they have family support in the home. The current study examines the association between social success upon school entry and teacher‐ratings of school readiness as assessed by the Brief Early Skills and Support Index (BESSI), controlling for language ability. Importantly, social success was assessed using a "child's‐eye view" with peer‐reported assessments of both social preference and reciprocated friendships. A total of 244 children (131 boys, M age = 61 months, SD = 4.78 months) in their first year of formal schooling participated. Child school readiness was found to be important for social preference, with the association being more marked for boys versus girls. Family support was the only independent predictor of children's reciprocated friendships. The use of the BESSI, with its broad scope compared to other measures of school readiness, highlights the importance of focusing both on a child's cognitive and socio‐emotional skills at school entry and their family support when exploring the association of school readiness to children's social success at the transition to formal schooling.